Catch-up tecnológico e superaç\~ao da armadilha da renda média: O caso da China no setor de semicondutores - Uallace Moreira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This discussion paper analyzes the catching-up and leapfrogging strategies implemented in China as a mechanism to overcome the middle-income trap. For this, it adopts the theoretical and methodological framework of the sectorial innovation system and the technological catch-up according to the technological life cycle of the product. This framework has proven to be efficient in promoting greater insertion of countries in the most advanced technological frontiers, breaking the limits that impede success in the path of economic development. In this sense, in this study, the semiconductor sector was analyzed as a case study, mainly because it is a sector that is on the technological frontier and has become even more relevant with the growth of what is conventionally called Industry 4.0. The strategic role that the semiconductor sector has achieved in the international economy has also become the target of technological disputes between China and the US. Analyzing the historical trajectory of policies implemented in China for the development of semiconductors, it appears that there are elements that point to the fact that, despite its limitations, the country has made considerable progress, which allows us to affirm that the future of China's semiconductor industry is promising.
Keywords: L52; O3; F23; 330; semiconductors; sectoral system of innovation; technological catch-up; short-cycle technology sectors